Laquinimod ameliorates excitotoxic damage by regulating glutamate re-uptake - Antonietta Gentile; Alessandra Musella; Francesca De Vito; Diego Fresegna; Silvia Bullitta; Francesca Romana Rizzo; Diego Centonze; Georgia Mandolesi (Journal of Neuroinflammation, 2018)
Abstract Background Laquinimod is an immunomodulatory drug under clinical investigation for the treatment of the progressive form of multiple sclerosis (MS) with both anti-inflammatory and neuroprotective effects. Excitotoxicity, a prominent pathophysiological feature of MS and of its animal model, experimental autoimmune encephalomyelitis (EAE), involves glutamate transporter (GluT) dysfunction in glial cells. The aim of this study was to assess whether laquinimod might exert direct neuroprotective effects by interfering with the mechanisms of excitotoxicity linked to GluT function impairments in EAE. Methods Osmotic minipumps allowing continuous intracerebroventricular (icv) infusion of laquinimod for 4 weeks were implanted into C57BL/6 mice before EAE induction. EAE cerebella were taken to perform western blot and qPCR experiments. For ex vivo experiments, EAE cerebellar slices were incubated with laquinimod before performing electrophysiology, western blot, and qPCR. Results In vivo treatment with laquinimod attenuated EAE clinical score at the peak of the disease, without remarkable effects on inflammatory markers. In vitro application of laquinimod to EAE cerebellar slices prevented EAE-linked glutamatergic alterations without mitigating astrogliosis and inflammation. Moreover, such treatment induced an increase of Slcla3 mRNA coding for the glial glutamate–aspartate transporter (GLAST) without affecting the protein content. Concomitantly, laquinimod significantly increased the levels of the glial glutamate transporter 1 (GLT-1) protein and pharmacological blockade of GLT-1 function fully abolished laquinimod anti-excitotoxic effect. Conclusions Overall, our results suggest that laquinimod protects against glutamate excitotoxicity of the cerebellum of EAE mice by bursting the expression of glial glutamate transporters, independently of its anti-inflammatory effects.